Procedural order inspection of the site - Цимбалюк, Валерій Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article examines for the examination of the scene as one of the most complex investigation and its remedial order execution.